Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Dinas Koperasi dan UKM Kabupaten Lebak - Safitri Putri Derajat; Jajuli Jajuli; Muhammad Zambri (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
This study aims to determine the effect of motivation and job satisfaction on employee performance at the Cooperatives and SMEs Office of Lebak Regency. The research problem stems from the persistent low motivation of employees and suboptimal job satisfaction, which impacts performance. This study used a quantitative method with a descriptive analytical approach. The sample size was 46 employees, selected using a saturated sampling technique. The research instrument, a questionnaire, was analyzed using validity and reliability tests, multiple linear regression, t-tests, and F-tests using SPSS. The results of the study indicate that motivation has a significant effect on employee performance, whilst job satisfaction also has a significant effect on employee performance. Consequently, motivation and job satisfaction simultaneously have a significant effect on employee performance. These findings suggest that motivation and job satisfaction are key factors in efforts to improve employee performance  at the Department of Cooperatives and UKM  in Lebak Regency.